Islamic Studies In Japan An Historical Overview - Kojiro Nakamura (Al-Jami'ah: Journal of Islamic Studies, 1991)
I would like to take "Islamic studies" here broadly as meaning the study of the Muslim world as well as of Islam as a religion. Then it goes more than a century back to the middle of the 19th century. Let me divide its history into four periods: First Period, 1868 – 1930 Second Period, 1930-1945 Third Period, 1945- 1970 Fourth Period,1970- present (I) First Period (1868 - 1930) This is a period of preparation. After the Meiji Revolution, Japan opened the door to foreign countries and launched to modernize the country, discarding the isolation policy of the Tokugawa feudal government. The Japanese began traveling abroad, either to study Western civilization or for political, diplomatic, or economic reasons. Foreigners also came in. The Japanese went not only to Europe and America, but also to China, India, Southeast Asia, and the Middle East, where they mingled with Muslims and encountered Islam. Yamada Torajiro and Ariga Bunpachiro, said to be the first Japanese Muslims, entered the faith either abroad - Yamada in the Ottoman Turkey, Ariga in India - or after returning to Japan.